Renin–angiotensin system blocker use and the risk of acute kidney injury after colorectal cancer surgery: a population-based cohort study. Issue 11 (21st November 2019) - Slagelse, Charlotte; Gammelager, H; Iversen, Lene Hjerrild; Liu, Kathleen D; Sørensen, Henrik T Toft; Christiansen, Christian F
Abstract : Objectives: It is unknown whether preoperative use of ACE inhibitors (ACE-I) or angiotensin receptor blockers (ARBs) affects the risk of acute kidney injury (AKI) after colorectal cancer (CRC) surgery. We assessed the impact of preoperative ACE-I/ARB use on risk of AKI after CRC surgery. Design: Observational cohort study. Patients were divided into three exposure groups—current, former and non-users—through reimbursed prescriptions within 365 days before the surgery. AKI within 7 days after surgery was defined according to the current Kidney Disease Improving Global Outcome consensus criteria. Setting: Population-based Danish medical databases. Participants: A total of 9932 patients undergoing incident CRC surgery during 2005–2014 in northern Denmark were included through the Danish Colorectal Cancer Group Database. Outcome measure: We computed cumulative incidence proportions (risk) of AKI with 95% CIs for current, former and non-users of ACE-I/ARB, including death as a competing risk. We compared current and former users with non-users by computing adjusted risk ratios (aRRs) using log-binomial regression adjusted for demographics, comorbidities and CRC-related characteristics. We stratified the analyses of ACE-I/ARB users to address any difference in impact within relevant subgroups. Results: Twenty-one per cent were ACE-I/ARB current users, 6.4% former users and 72.3% non-users. The 7-day postoperative AKI risk for current, former and non-users was 26.4% (95% CI 24.6% to 28.3%), 25.2% (21.9% to 28.6%) and 17.8% (17.0% to 18.7%), respectively. The aRRs of AKI were 1.20 (1.09 to 1.32) and 1.16 (1.01 to 1.34) for current and former users, compared with non-users. The relative risk of AKI in current compared with non-users was consistent in all subgroups, except for higher aRR in patients with a history of hypertension. Conclusions: Being a current or former user of ACE-I/ARBs is associated with an increased risk of postoperative AKI compared with non-users. Although it may not be a drug effect, users of ACE-I/ARBs should be considered a risk group for postoperative AKI.